ISU GENDER DALAM PROFESI PUBLIC RELATIONS DI INDONESIA - Dio Herman Saputro; Satya Candrasari (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2018)
Public relations in Indonesia still often perceived as female profession and suited for women so then this profession is slow down and degradation. Gender is became a host issues in this problem. The study of gendered issues in public relations have concducted by reseacher from the part of the world have already showed inequality gender phenomenon. This research tries to disscuss gender study in the domain of public relations in Indonesia with literarure review data collecting. The Results show that gender issues in public relations profession have to keep monitored because it has already demonstrated discrmination gender and degrated to the public relations profession.Many parties that responded to the gender problems because of just the different perception but the development of public relations profession also is influenced by the structure national culture, type and field of industry and bussiness needs. Keywords: Gender, Profession, Public Relations, Jakarta, Issues